The Erzurum Branch of Teşkilat-ı Mahsusa - Sahakyan, Vera (History and Culture, 2026)
During the First World War, the Russian-Turkish border, also known as the Caucasian Front or Eastern Front, extended from the Black Sea to the northern regions of Iran. The defense of this front was assigned to the Ottoman Third Army, led by Mahmud Kâmil Pasha. The Ottoman Empire had a strategic interest in the Caucasus region, aiming to maintain influence in the area if Russian power were to be established there. Additionally, they sought to utilize an Independent North Caucasus as a buffer in case of changes in the geopolitical situation. To further these goals, between August and October of 1914, regiments supporting the Ottoman army were dislocated along the Russian-Turkish border. These regiments were coordinated by the Istanbul center of the Teşkilat-ı Mahsusa organization. Three headquarters were established in strategic locations: Erzurum, Van, and Trabzon. This strategic planning and organization were indicative of the Ottoman Empire’s efforts to assert control over the Caucasus region and to prepare for potential conflicts and shifts in power dynamics during the First World War. Such strategic planning testifies to the Ottoman Empire’s efforts to establish control over the Caucasian region and to prepare for potential conflicts and shifts in power dynamics during the First World War. Within the framework of the article, we aimed to explore recent publications concerning the organization known as Teşkilat-I Mahsusa, which has gained significant traction. We sought to shed light on the activities of the Erzurum branch, focusing on key details from the memoirs of Arif Cemil (Denker) and Ebulhindili Cafer Bey.